Malaysian Agricultural Biotechnology: An Outlook on Recent Developments, Regulatory Framework and Impediments - Ismail, Suzi Fadhilah (INSI Publications, 2012)
Biotechnology has been internationally acknowledged as the scientific and technological revolution of the 21stcentury. As far as Malaysia is concerned, biotechnology is set to be a major contributor to its economic growth. Although it is still in its infancy stage, its potential is enormous. With the nation’s rich biodiversity, cost-competitive labour and strong agricultural base, Malaysia stands to gain from its biotechnological development that will position the country as a key global player by 2020. The country aims to gain a slice of the lucrative global biotechnology market. Thus, this paper examines the growth and development of Malaysia’s biotechnological sector, focusing on the agricultural biotechnology. Itessentially covers the discussion on the Malaysian National Biotechnology Policy (NBP), the legal and regulatory framework affecting the agricultural biotechnology in Malaysia which includes patent law and plant variety rights, as well as the impediments encountered by the industry to the success of biotechnological R&D.